Examine and Compared MMPI Profile of Veterans With Chronic Pain With Patients With Chronic Pain - N. Vakili; H. Kazemi; H. Koolivand; F. Rezaei; N. Ghasemi (Afarand Scholarly Publishing Institute, 2013)
Introduction: chronic pain experience is influenced by complex interplay of biopsychosocial factors. Patients with chronic pain have special emotional and psychological context. Prevalence of chronic pain in veterans has confirmed by various studies. Aim: this study examines and compared the psychological profile of patients with chronic pain with psychological profile of veterans with chronic pain. Method: this study is descriptive -analytic and comparative. This study was conducted in Shefa Pain Clinic on 100 patients with chronic pain and 100 veterans with chronic pain who were randomly selected. MMPI was used to investigate the psychological profile. Results: the results showed that there was significant difference between groups in all scales (p< 0.05) . Average scores in all indices in veterans group were significantly increased in comparison with chronic pain patients group. The most significant difference was observed in the hypochondria and depression. Discussion: the results of this study are based on certain psychological problems in veteran with chronic pain. Also results suggest specific psychological profile, characterized by an elevation of the three scales hypochondria, depression and hysteria in patients with chronic pain.